An electrospray ionization mass spectrometry study of azidoacetic acid/transition metal complexes. (17th May 2017) - Pinto, Vítor S.; Marques, Susana C. R.; Rodrigues, Paula; Barros, M. Teresa; Costa, M. Lourdes; Langley, G. John; Fernandez, M. Tereza; Cabral, Benedito J. C.; Duarte, M. Filomena; Couto, Narciso
Abstract : Rationale: The complexation behavior of transition metals with organic azides by electrospray ionization (ESI) tandem mass spectrometry (MS/MS) is not completely understood. In this study, fragmentation patterns of complex ions having azidoacetic acid coordinated to Ni/Co/Fe were elucidated. The role of transition metals in the mediation of ligand rearrangements in gas phase is experimentally supported. Methods: The complexation of some transition metals, nickel, cobalt and iron, by azidoacetic acid was studied by means of ESI and MS/MS. Fragmentation patterns were discerned via consecutive MS/MS experiments on an ion trap mass spectrometer and confirmed by high‐resolution (HR) Fourier transform ion cyclotron resonance MS. Density functional theory (DFT) calculations were used to characterize the major ions observed in MS. Results: Only singly positively charged complex ions were detected presenting various stoichiometries. MS/MS and theoretical calculations allowed us to confirm assignments and coordination sites. Structural evidence suggested that the azidoacetic acid can behave as monodentate and/or bidentate and coordination through the oxygen and nitrogen atoms are both possible. Experimental evidence strongly points to a role of Ni/Co/Fe, in oxidative state (I), in mediating C–C bond activation in the gas phase. Conclusions: MS/MS and HRMS experiments were able to elucidate azidoacetic acid complexation with Ni/Co/Fe and several gas‐phase processes involving metal reduction and rearrangements. The definition of the coordination pattern dictated by the competition between the nitrogen and the oxygen atoms is also dependent on the metal centre in a very dynamic process. Copyright © 2017 John Wiley & Sons, Ltd.